An electrospun polyurethane scaffold-reinforced zwitterionic hydrogel as a biocompatible device. Issue 12 (28th February 2020) - Liu, Sihang; Ma, Jun; Xu, Liangbo; Lin, Weifeng; Xue, Weili; Huang, Mei; Chen, Shengfu
Abstract : An electrospun scaffold-reinforced zwitterionic hydrogel achieved both high tensile strength and mechano-induced self-enhancement while maintaining excellent hemocompatibility. Abstract : Although zwitterionic hydrogels exhibit excellent hemocompatibility, their extremely low tensile strength is an obstacle for their use in blood-contacting devices. Electrospun fiber scaffold-reinforced zwitterionic hydrogels are a possible solution to overcome the challenges of both mechanical strength and hemocompatibility. In this work, electrospun polyurethane (ePU) fiber scaffold-reinforced sulfobetaine methacrylate (SBMA) hydrogels (SRgels) were prepared. The SRgels exhibited 4.7 ± 0.5 MPa tensile fracture stress, while the interpenetration between the hydrogel and the fiber scaffold remained intact even under 2.8 MPa tensile stress at 3.0 mm mm −1 strain load; this confirms that the SRgels maintain excellent hemocompatibility for both blood cell adhesion and fibrinogen adsorption under physiological dynamic loading and that dynamically structural matching is achieved between the scaffold and the zwitterionic hydrogels. Mechano-induced self-enhancement was also observed after preloading more than 2.0 mm mm −1 tensile strain to resist fracture. In short, the preparation of SRgels can enable zwitterionic hydrogels to meet the requirement for mechanical strength in bio-applications as blood-contacting devices.